Performance and Blood Chemistry as Affected by Inclusion of Moringa Oleifera Leaf Meal in Broiler chicks Diet (Journal of Veterinary Medicine and Animal Production, 2022)
U. of K. J. Vet. Med. Anim. Prod., Vol. 5, Issue 2 (2014) p 58-65ISSN: 24345658Performance and Blood Chemistry as Affected by Inclusion of MoringaOleifera Leaf Meal in Broiler chicks DietSafa M.A. El Tazi* and Ibrahim M. Tibin1AbstractThe effect of Moringa oleifera leaf meal (MOLM) on the performance and blood chemistryof broiler chicks’ diets were investigated. A total of one-hundred and sixty one-day old, unsexed(Ross) broiler chicks were randomly divided into four experimental groups. Each group was furthersubdivided into five replicates at the rate of eight chicks per pen in randomized complete blockdesign. Four levels of Moringa oleifera leaf meal (0.0, 3, 5 and 7%) were fed during theexperimental period for 7-weeks duration. Birds fed on MOLM gained significantly (P